Personal protective eyewear usage among industrial workers in small-scale enterprises - Tahra AlMahmoud; Ismail Elkonaisi; Michal Grivna; Fikri M. Abu-Zidan (BMC, 2020)
Abstract Background Work-related eye injury causes significant vision loss. Most of these injuries are preventable with appropriate eye safety practices. We aimed to study industrial workers' perceptions of Personal Protective Eyewear (PPE) and its usage in a high income developing country. Methods A field-based cross-sectional study in small-scale industrial entities was performed in Al-Ain City, UAE during the period of October 2018 to June 2019. Five hundred workers completed a pretested structured questionnaire. Data on demographics, occupational history, work hazard awareness, and PPE usage at their work place were collected. Results The workers were experienced, with a median of 15 years in practice. The majority (80%) learned their work skills through apprenticeship (i.e., on-the-job) training. Most (85%) were involved with activities presenting eye injury risk, and were highly aware of this. None of the workers used safety goggles or glasses all the time for activities that need PPE usage. Five percent never used PPE in the workplace. The main reason for not using PPE was the work demands (95%) and poor vision through the lenses (75%). Young age and less work experience were associated with less PPE usage (P < 0.0001). Wearing prescription spectacles had a positive correlation with usage of safety goggles (P = 0.005) and a negative correlation with welding helmet usage (P < 0.0001). Conclusions There was a high level of awareness about the value of PPE in the workplace which was not translated into real practice. Educational programs promoting eye safety practices and proper PPE usage should be adopted by workers in small-scale industrial settings.